Effect of Intra Row Spacing and Nitrogen on Some Yield Characters ofPearl Millet (Pennisetum glaucum (L.) R.Br.) in Jigawa State, Nigeria. (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
trials were conducted during 2020 rainy season at Birnin Kudu Local Government (11°21’ 48.4”N, 9°52’ 35.3”E) and Jikas area in Maruta ward under Gwaram Local Government (11°28’ 16.4”N, 9°27’ 33.2”E). Both sites were located in Jigawa State and fall within Sudan Savannah agro ecological zone of Nigeria; The experiment evaluated the performance of pearl millet as affected by intra row spacing and nitrogen levels. The treatments consisted of three intra row spacing (25, 50 and 75cm) and four nitrogen levels (0, 40, 80 and 120kg N/ha). The treatments were factorally combined and laid out in a randomized complete block design and replicated three times. Panicle diameter, panicle weight, Stover yield, 1000 grains weight, grain yield and harvest index were observed as yield characters. Results revealed that, intra-row spacing had significant (P